Lipoprotein Signal Peptide as Adjuvants: Leveraging Lipobox-Driven TLR2 Activation in Modern Vaccine Design - Muhammad Umar; Haroon Afzal; Asad Murtaza; Li-Ting Cheng (Vaccines)
Toll-like receptor 2 (TLR2) signaling is a pivotal component of immune system activation, and it is closely linked to the lipidation of bacterial proteins. This lipidation is guided by bacterial signal peptides (SPs), which ensure the precise targeting and membrane anchoring of these proteins. The lipidation process is essential for TLR2 recognition and the activation of robust immune responses, positioning lipidated bacterial proteins as potent immunomodulators and adjuvants for vaccines against bacterial-, viral-, and cancer-related antigens. The structural diversity and cleavage pathways of bacterial SPs are critical in determining lipidation efficiency and protein localization, influencing their immunogenic potential. Recent advances in bioinformatics have significantly improved the prediction of SP structures and cleavage sites, facilitating the rational design of recombinant lipoproteins optimized for immune activation. Moreover, the use of SP-containing lipobox motifs, as adjuvants to lipidate heterologous proteins, has expanded the potential of vaccines targeting a broad range of pathogens. However, challenges persist in expressing lipidated proteins, particularly within heterologous systems. These challenges can be addressed by optimizing expression systems, such as engineering E. coli strains for enhanced lipidation. Thus, lipoprotein signal peptides (SPs) demonstrate remarkable versatility as adjuvants in vaccine development, diagnostics, and immune therapeutics, highlighting their essential role in advancing immune-based strategies to combat diverse pathogens.